From fossil fuels to renewables: Studies on the effects of resource endowments and climate policy on economic outcomes - Ana Maria Montoya Gómez (ifo Institut - Leibniz-Institut für Wirtschaftsforschung an der Universität München, 2020)
This doctoral thesis, organized in three self-contained chapters, provides an analysis of the economic effects associated with the extraction of natural resources and the transition from an economy based on fossil fuel use to an economy relying primarily on renewable energy sources. Chapter 1 assesses the question of a potential resource curse in Colombia by analyzing the effect of oil production on different indicators of the development level of municipalities: school enrollment rates, infant mortality rates, and average results of the nationwide school-leaving examination. Moreover, it considers the role that local institutions play in this context. Chapter 2 analyzes how greenhouse gas emissions of companies in OECD and BRICS countries have developed in response to policies aiming at reducing fossil fuel use by providing financial incentives to expand renewable energy adoption and to improve energy efficiency. Chapter 3 provides an extended Input-Output approach to study the economic effects of increased investments in renewable energies and energy efficiency measures. The methodology is tailored to make it applicable to subnational regions and accounts for the scarcity of financial resources and factors of production. Furthermore, Chapter 3 applies the methodology to quantify the effects of an intended energy transition in three German districts. – – Diese aus drei eigenständigen Kapiteln bestehende Dissertation bietet eine Analyse der wirtschaftlichen Auswirkungen der Extraktion natürlicher Ressourcen und des Übergangs von einer auf fossilen Brennstoffen basierenden Wirtschaft zu einer Wirtschaft, die hauptsächlich auf erneuerbaren Energiequellen beruht. Kapitel 1 beschäftigt sich mit der Frage, ob in Kolumbien ein Ressourcenfluch vorliegt. Zu diesem Zweck werden die Auswirkungen der Ölförderung auf verschiedene Indikatoren für das Entwicklungsniveau der Kommunen analysiert: Schuleinschreibungsraten, Kindersterblichkeitsraten und durchschnittliche Ergebnisse der landesweiten Schulabschlussprüfungen. Darüber hinaus wird die Rolle lokaler Institutionen in diesem Zusammenhang betrachtet. Kapitel 2 untersucht, wie sich die Treibhausgasemissionen von Unternehmen in OECD- und BRICS-Ländern als Reaktion auf Politikmaßnahmen zur Reduktion des Verbrauchs fossiler Brennstoffe entwickelt haben. Die betrachteten Politikmaßnahmen umfassen finanzielle Anreize zur verstärkten Anwendung erneuerbarer Energien und zur Verbesserung der Energieeffizienz in Unternehmen. Kapitel 3 bietet einen erweiterten Input-Output-Ansatz zur Untersuchung der Wertschöpfungs- und Beschäftigungseffekte von Investitionen in erneuerbare Energien und Energieeffizienzmaßnahmen. Der Ansatz wurde so weiterentwickelt, dass er auf subnationale Regionen anwendbar ist, und berücksichtigt die Knappheit an finanziellen Ressourcen und Produktionsfaktoren. Darüber hinaus wendet Kapitel 3 die Methodik zur Quantifizierung der Auswirkungen einer beabsichtigten Energiewende in drei deutschen Landkreisen an.
Keywords: D02; C67; H23; H32; H41; H75; O10; Q32; Q42; Q43; Q48; Q54; Q58; R11; R15; 330; natural resource curse; economic development; subnational analysis; institutions; education; health; climate policy evaluation; greenhouse gas emissions; cross-country micro panel data; companies; firms; renewable energy; factors of production; input-output table; macroeconomic effects; crowding out effects; Natural resource curse; economic development; subnational analysis; institutions; education; health; climate policy evaluation; greenhouse gas emissions; cross-country micro panel data; companies; firms; renewable energy; factors of production; input-outpput table; macroeconomic effects; crowding out effects